Ford Madox Ford's literary contacts - Skinner, Paul (International Ford Madox Ford studies ;, 2007)
The controversial British writer Ford Madox Ford (1873-1939) is increasingly recognized as a major presence in early twentieth-century literature. This series of International Ford Madox Ford Studies was founded to reflect the recent resurgence of interest in him. Each volume is based upon a particular theme or issue; and relates aspects of Ford's work, life, and contacts, to broader concerns of his time. The present book is part of a large-scale reassessment of his roles in literary history. Ford is best-known for his fiction, especially The Good Soldier, long considered a modernist masterpie.